Analysis of Loss of Essential Power System Reported in Nuclear Power Plants - Andrija Volkanovski; Miguel Peinador Veira (Science and Technology of Nuclear Installations)
The essential power supply system is important for the nuclear safety and accident mitigation of the currently operating nuclear power plants. This system provides electrical power to the essential instrumentation and control systems of the nuclear power plant when all alternate current power sources are lost. This event is known as station blackout (SBO) event. Operational events of failure or deficiency of the essential power supply system are analyzed in this paper. The relevant events were searched and identified in four databases of operational events. The report includes events identified in French SAPIDE and German VERA operational events records for the time period 1996 to 2015. The International Atomic Energy Agency (IAEA) IRS and Nuclear Regulatory Commission (NRC) LER operational events databases were screened for relevant events that occurred in the period between 2000 and 2016. In total, 308 relevant events are identified in the SAPIDE, 103 in VERA, 56 in LER, and 15 in IRS operational events database. Classification and in-depth analysis were done on the identified events considering the following predefined categories: the plant status during the event, circumstances, affected equipment, cause of the event (direct and root), and implications of the event on plant safety. Main findings from the evaluation of the events are presented. Observations of the causes resulting in the events and potential actions that can decrease the number and consequences of the events are presented.